Species composition, structure, and carbon stocks of coffee agroforestry systems in East Java, Indonesia - Hamdi Hamdi; Moh Ardani; Lutfi Pramukyana; Dwika Nano Hariyanto; Ida Rosita; Yosie Syadza Kusuma (Talenta Publisher, 2026)
Coffee agroforestry systems (CAF) offer an important opportunity to maintain agricultural productivity while enhancing ecosystem services by integrating shade trees and perennial crops. This study aimed to characterize vegetation composition and structure and to estimate carbon stocks in CAF in Panti District, Jember Regency, East Java. A total of 12 nested plots were established to assess vegetation composition, structure, and carbon stocks. The results showed that 17 species belonging to 13 families were identified. The highest Importance Value Index (IVI) at the seedling and sapling levels was Coffea canephora, while at the pole and tree levels, Hevea brasiliensis dominated. Species diversity (H′ = 0.60 1.77) and evenness (E = 0.50–0.81) increased from the seedling to tree stages. The regeneration structure and diameter class distribution of the stand exhibited an inverse J-shaped distribution pattern. The total carbon stock was 161.3 Mg C ha⁻¹, equivalent to 591.7 Mg CO₂e ha⁻¹. Shade-tree aboveground biomass represented the largest carbon pool (93.9 Mg C ha⁻¹; 58.2%), followed by soil organic carbon (36.2 Mg C ha⁻¹; 22.4%), while coffee shrubs accounted for only 8.2 Mg C ha⁻¹ (5.1%). These findings demonstrate that carbon accumulation in this CAF is predominantly biomass-driven rather than soil-driven.